AKTIVITAS PETANI PADA MUSIM PACEKLIK (PILIHAN RASIONAL PETANI DESA WUDI KECAMATAN SAMBENG KABUPATEN LAMONGAN) - Fahmi Anas; Halimur Rosyid (Universitas Islam Darul Ulum Lamongan, 2021)
The problem in this study is how farmers survive in the middle of the low season in Wudi Village, Sambeng District, Lamongan Regency and how farmers work to meet their daily needs. The research method used by the researcher is descriptive qualitative. In this study, the researchers determined the informants by means of a snowball, the informants in this study were the Wudi Village Apparatus, farmers and also people who migrated. Collecting data through observation, interviews, and documentation. The theory that the researcher analyzes in analyzing the phenomenon of farmer activities during the low season and the choice of work of farmers in Wudi Village, Sambeng District, Lamongan Regency is James' Rational Choice Theory. S Colemen. The results showed that the way the farmers worked for the necessities of life which was carried out during the low season was by raising oxen (private oxen and neighboring oxen), helping neighbors (other farmers), and also migrating to the city.